Nove tehnologije, spremenjena občinstva, stare vrednote - Jontes, Dejan (Teorija in praksa, 2010)
The paper focuses on the question of journalistic identity from the perspective of technological and social changes. The author tries to reveal how the debate about the potential of online journalism influences the process of defining and redefining journalism, its standards and values. To answer this question, texts about journalism are analysed: the analysis focuses on interviews and commentaries about journalism in Slovenian quality press in 1995, 2005 and 2006 (the papers Delo, Dnevnik, Večer and political magazines Mag and Mladina are included). The analysis shows how journalism is defined and organised as a profession and what constitutes good or bad journalism in a certain historical period. It is based on a premise that journalists create and share interpretations of events and social change through discourse and thus make sense of their professional life.
Keywords: Journalism; Novinarstvo; Values; Vrednote; Identiteta; Identity; New technologies; Nove tehnologije